2008
DOI: 10.1097/tp.0b013e3181722f75
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age and Cold Ischemia Interact to Produce Inferior 90-Day Liver Allograft Survival

Abstract: These findings suggest that older donor age and prolonged cold ischemia interact to increase liver allograft failure at 90 days. Proposals to expand regional sharing of older livers should be regarded with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 24 publications
2
44
2
1
Order By: Relevance
“…4 Reese and colleagues described increased donor age as well as cold ischemia times as factors negatively influencing 90-day allograft survival. 12 These findings are at variance with our study, in which 30-day survival did not significantly differ between liver transplant recipients of group A and B donors (P = .08). Many studies have shown the inferiority of organs (including liver) obtained from deceased donors to those from living donors.…”
Section: Discussioncontrasting
confidence: 57%
“…4 Reese and colleagues described increased donor age as well as cold ischemia times as factors negatively influencing 90-day allograft survival. 12 These findings are at variance with our study, in which 30-day survival did not significantly differ between liver transplant recipients of group A and B donors (P = .08). Many studies have shown the inferiority of organs (including liver) obtained from deceased donors to those from living donors.…”
Section: Discussioncontrasting
confidence: 57%
“…No significant differences in baseline median HCV RNA load were observed (5.4 log 10 IU/ml) ( Table 1) 15 . Additional clinical parameters previously reported to affect HCV replication or allograft survival, such as donor age (AM: median, 55 years; range 45–69 years; PM: median, 44 years; range, 29–64) 16 , cold-ischemia time 17 , duration and time of operation 18 were comparable in the AM or PM groups ( Table 1). In four of six patients (#3, 7, 8 and 11) in the AM group, a viral rebound toward pre-transplant levels was observed during the time of study ( Figure 2A).…”
Section: Resultsmentioning
confidence: 84%
“…De especial interés es la combinación de un tiempo de isquemia prolongado con el resto de variables del donante, por lo que es preciso intensificar esfuerzos para que se minimice en la medida de lo posible cuando coexiste algún otro factor de riesgo 79,80 . Esto determina una mayor puntuación en las escalas de valoración del riesgo y una mayor probabilidad de desarrollo de lesión de isquemia/reperfusión, y por ende, de disfunción del injerto.…”
Section: Análisis De La Existencia De Límites Biológicos Para La Donaunclassified